(untitled) (Olhares, 2020)
This work reports the creation and assembly process of the theatrical performance Parahyba Rio Mulher. The show is dedicated to telling stories of past and present women and reveal not only a history of silence and violence against women that has gone through generations, but also evoking ancestry to revere the strength of the sacred feminine that connects us and invites us to resist and continue our journeys. Thus, the rites define their paths. Cast and audience women from Brazil and the rest of the world have their trajectories connected to that of Anayde Beiriz, a woman who defied standards in a conservative Paraiba society of almost a hundred years ago, and who was the protagonist of the episode that led to the change of name of Paraíba state capital from Parahyba to João Pessoa, in the midst of the 1930’s Revolution.